The role of unidirectional surface roughness on the regularity of LIPSS generated on stainless steel using femtosecond lasers - Diego Gallego; Isabel Ayerdi; Aldara Pan; Santiago M. Olaizola; Ainara Rodriguez (Scientific Reports)
Abstract Laser induced periodic surface structures (LIPSS) are directional and periodic nanostructures generated in most materials when irradiated with linear polarized laser beams under certain irradiation conditions. LIPSS present a wide range of well-known properties and applications, but their implementation on the optical field is restricted because of their low regularity in comparison to microstructures fabricated by other methods. Surface roughness has an impact on LIPSS regularity, as it can promote their generation acting as a seed or influence their orientation in favor of the roughness direction. During this study, the influence of the surface roughness and its orientation on the LIPSS regularity has been explored by means of DLOA (dispersion of the LIPSS orientation angle), for stainless steel with arithmetic mean height (Sa) parameter ranging from a few nanometers to one micrometer. The experimental results have proven that the magnitude and a preferred direction of substrate roughness affect the coherence and orientation of the LIPSS.